2017
DOI: 10.1007/jhep09(2017)152
|View full text |Cite
|
Sign up to set email alerts
|

Higher order gravities and the Strong Equivalence Principle

Abstract: We show that, in all metric theories of gravity with a general covariant action, gravity couples to the gravitational energy-momentum tensor in the same way it couples to the matter energy-momentum tensor order by order in the weak field approximation around flat spacetime. We discuss the relation of this property to the Strong Equivalence Principle. We also study the gauge transformation properties of the gravitational energymomentum tensor.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…A natural idea would be to first relate universal coupling of the (quantum) spin-2 field to universal coupling of g, and then argue that SEP-GR follows. Note, however, that universal coupling of g might indeed be viewed simply as one of the requirements for SEP-GR, but there may be other requirements as well (similarly, see Ortín (2017)). For example, one might want to additionally exclude certain types of (non-dynamical) fixed fields from the theory (e.g., fixed timelike vector fields), as they can violate Lorentz invariance.…”
Section: Lesson I: a Closer Look At The Equivalence Principlementioning
confidence: 99%
See 2 more Smart Citations
“…A natural idea would be to first relate universal coupling of the (quantum) spin-2 field to universal coupling of g, and then argue that SEP-GR follows. Note, however, that universal coupling of g might indeed be viewed simply as one of the requirements for SEP-GR, but there may be other requirements as well (similarly, see Ortín (2017)). For example, one might want to additionally exclude certain types of (non-dynamical) fixed fields from the theory (e.g., fixed timelike vector fields), as they can violate Lorentz invariance.…”
Section: Lesson I: a Closer Look At The Equivalence Principlementioning
confidence: 99%
“…In particular, self-coupling is necessary if any coupling to matter is to be included. Accordingly, WEP-like statements in this context also encompass that "gravitational binding energy of massive bodies will not modify their free-fall motion" (Ortín, 2017). 45 This suggests that the universal coupling reformulation-irrespective of how WEP-like it is-is indeed the most general or strongest possible reinterpretation of the equivalence principles (i.e., UC-Strong).…”
Section: Lesson I: a Closer Look At The Equivalence Principlementioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, analysis like that of Butcher et al [16] do not seem to leave the room for other solutions to the self-coupling problem. Specially interesting are the recent works on the self-coupling of higher derivative theories [16,18,19]. Whereas in [16,19] it was found that higher-derivatives theories bootstrap in the same sense than GR does, in [18], by working in first-order formalism, the author concluded that they do not unless one enforces "by hand" the condition that the connection is the Levi-Civita connection associated with the full metric.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we will study what are the minimal requirements to build a theory of massless gravitons and where the bifurcation appears. Additionally, we will answer two long standing questions about UG that are not well-understood in the literature yet -how does the equivalence principle arises in the theory [35] and what is the relation of its S-matrix with the one of GR.…”
Section: Introductionmentioning
confidence: 99%